2013
DOI: 10.1016/j.ymben.2012.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Three-step pathway engineering results in more incidence rate and higher emission of nerolidol and improved attraction of Diadegma semiclausum

Abstract: , Three-step pathway engineering results in more incidence rate and higher emission of nerolidol and improved attraction of Diadegma semiclausum, Metabolic Engineering, http://dx.doi.org/10.1016/j. ymben.2012.10.002 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
2
25
0
Order By: Relevance
“…Furthermore, the combination of both JA-induced volatiles and MeSA is important for the attraction of P. persimilis predatory mites towards Lima bean plants . In line with Houshyani et al (2013) (Houshyani et al, 2013) and has been found in P. xylostella-induced volatile blends from A. thaliana ; Supplementary materials Table S1). Other volatile compounds induced most strongly by feeding of P. xylostella caterpillars were β-mycrene and TMTT and, therefore, may contribute to the attraction of D. semiclausum parasitoids (Supplementary materials Table S1).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, the combination of both JA-induced volatiles and MeSA is important for the attraction of P. persimilis predatory mites towards Lima bean plants . In line with Houshyani et al (2013) (Houshyani et al, 2013) and has been found in P. xylostella-induced volatile blends from A. thaliana ; Supplementary materials Table S1). Other volatile compounds induced most strongly by feeding of P. xylostella caterpillars were β-mycrene and TMTT and, therefore, may contribute to the attraction of D. semiclausum parasitoids (Supplementary materials Table S1).…”
Section: Discussionsupporting
confidence: 82%
“…The microarray data indicated that the linalool synthase TPS10 gene was differentially expressed in response to feeding of both caterpillars and aphids at high density after 24 h compared to undamaged control plants, but not in response to dual insect infestation at low density (Chapter 6). Linalool has been reported to be an important attractant for D. semiclausum parasitoids (Houshyani et al, 2013) and induced biosynthesis of linalool could have influenced D. semiclausum preference for plants dually infested by caterpillars and aphids at high density. Results of Chapter 5 indicate that D. rapae parasitoids prefer volatiles emitted by dual-infested plants over plants infested by B. brassicae aphids alone, which is noteworthy.…”
Section: Plant-mediated Effects Of Dual Insect Attack On Indirect Defmentioning
confidence: 99%
“…Transformation of Col-3 plants used in this study was done by the insertion of 2 (in COX+) or 3 (in COX++) constructs, each containing the gene of interest ( COX-FaNes1 , FPS1L or HMGR1S ) (Figure 1a) and a selection-marker gene [17]. Quantitative RT-PCR showed de novo FaNES1 expression in the transgenic lines.…”
Section: Resultsmentioning
confidence: 99%
“…Quantitative RT-PCR showed de novo FaNES1 expression in the transgenic lines. FPS1L expression was at least 64-fold higher in COX + and COX++ and expression of HMGR1S was at least16-fold higher in COX++ lines than in Col-3 (the wild type) [17]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation